INDIAN KNOWLEDGE SYSTEMS AND MODERNITY: MILIEU OF INDIAN COMICS AND SUPERHEROES - Jash, Sambuddha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper seeks to trace the genesis of Indian comics and the superheroes portrayed in them as a site of serious critical thought. The composition of the initial crop of Indian comics is intricately connected to the study of traditional Indian mythology and its relevance to the eulogization of heroic ideals and spirit. It is deeply entrenched into the various genealogies of change that has been catalysing our own Indian knowledge systems. This has been done by providing a brief history of the development of Indian comics which at its initial stages was mostly a derivation of its western counterparts. Through an analysis of Amar Chitra Katha and the Raj Comics, I have tried to delve deeper into the construction of the ‘Indian Superhero’ and it being the point of departure from popular superheroes like Superman, Batman and others. The analytical framework of the paper is the fact that the advent of the Indian Superhero was not only a necessity of the Indian comics’ readership market but also a metaphorical moment that shares tangential relationship with the political changes and economic liberalization.